Communication Prototype for Post-Stroke Patients Using Electrooculography (EOG) - Rakhma, Ukhti Alifah Aulia; Loniza, Erika; Kartika, Wisnu (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
Background this prototype is intended for post-stroke patients experiencing disabilities in their daily activities, particularly in communication with others. The challenge they face is difficulty in communication, leading to a diminished quality of life for post-stroke patients. The purpose of innovating this communication aid prototype is to facilitate communication between post-stroke patients and caregivers. The method employed in the post-stroke communication aid prototype utilizes Electrooculography (EOG) signals generated from eye muscle movements during eye gazes, captured by the MaM Sense sensor. The variation in Analog-to-Digital Converter (ADC) values in the MaM Sense sensor is exploited to produce various forms of EOG signals. The resultant command signals from this method are processed by a microcontroller and displayed on a 20 x 4 Character LCD. Testing was conducted on 9 healthy individuals, comprising 5 males and 4 females. To ensure the prototype's functionality, testing was also performed on 1 post-stroke patient. The success rate of MaM Sense sensor readings was 80.5% for the 4 communication modes employed, involving 4 eye gaze movements: right gaze, left gaze, upward gaze, and downward gaze. Thus, the post-stroke communication aid prototype proves effective in assisting communication for post-stroke patients and aiding caregivers in understanding the patients' desires. In the future, a wireless system may be implemented for the acquisition of EOG signals attached to the face to minimize the use of cables.